Who receives post‐acute care? Characteristics of national population and field test sample. Issue 4 (2nd March 2022) - Rodriguez, Anthony; Edelen, Maria O.; McMullen, Tara L.; Ahluwalia, Sangeeta C.; Chen, Emily K.; Dalton, Sarah E.; Paddock, Susan; Saliba, Debra; Mandl, Stella; Mota, Teresa
Abstract: Background: Each year millions of Medicare beneficiaries in the United States receive post‐acute care (PAC) in skilled nursing facilities (SNFs), inpatient rehabilitation facilities (IRFs), long‐term care hospitals (LTCHs), and home health agencies (HHA). We describe, overall and by PAC setting, the national population of facilities and patients, evaluate the representativeness of a national field test sample, and describe patient characteristics in the national field test sample. Methods: We analyzed the 2016 Provider of Service file, 2016 patient assessment data reported by PAC providers to Centers for Medicare & Medicaid, and data collected from PAC providers participating in a national field test. National data included 27, 234 PAC settings and 5, 033, 820 beneficiaries receiving PAC. The national field test sample consisted of 143 facilities across 14 markets with 25–30 patients sampled from each facility (n = 3669). We describe PAC facility and patient characteristics for both the national and field test sample. Results: Nationally, PAC facilities were more likely for‐profit versus not for‐profit, have an average nurse‐to‐bed ratio between 1:10 to 1:1 (lowest in SNFs) and be in metropolitan versus other areas. PAC patients were more likely to be white, female, and 75–89 years of age; heart failure as a primary medical condition tended to be more common than stroke or sepsis. There was limited variability across setting types. In the national field test, patients in LTCHs demonstrated a greater likelihood of cognitive impairment, positive depression screening, bowel and bladder appliance use, higher rates of medication drug classes taken, and use of therapeutic diets and IV medications. Conclusion: The national field test facility and patient samples were fairly representative of the national population overall and across settings with a few exceptions. Moreover, differences according to PAC setting on patient characteristics in the national field test aligned with general differences in patient populations.